2019
DOI: 10.17140/aftnsoj-5-152
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro-Evaluation of the Antioxidant Properties of Moringa Oleifera and Camelia Sinensis Leaves

Abstract: IntroductionMoringa oleifera and Camellia sinensis are edible plants widely distributed in parts of South East of Nigeria. Both are used as a beverage and medicinal plant in the treatment of several ailments by alternative medical practitioners. The in vitro-antioxidant properties of both Moringa oleifera and Camelia sinensis leaves were investigated in the current study.. MethodPhytochemical analysis was carried out to evaluate the flavonoids and total phenolic contents of the plants crude extracts. Also, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…The obtained results demonstrated that the sample type influences the content of phenolic compounds recovered from moringa. Comparing our TPC values with available information in the literature, it was observed that results from the present study were at the same level as the values reported by Ilesanmi et al [39] for 80% aqueous methanolic extracts of M. oleifera leaves (541 ± 1 mg GAE/g dw), but higher than those reported by other researchers [40][41][42][43][44]. Indeed, our TPC findings were higher than those of M. oleifera trees found in the Menzel Lahbib (Gabes-Tunisia) region, whose values ranged from 80.9 ± 1.2 to 136 ± 8 mg GAE/g dw.…”
Section: Total Phenolic and Flavonoid Contentsupporting
confidence: 88%
See 2 more Smart Citations
“…The obtained results demonstrated that the sample type influences the content of phenolic compounds recovered from moringa. Comparing our TPC values with available information in the literature, it was observed that results from the present study were at the same level as the values reported by Ilesanmi et al [39] for 80% aqueous methanolic extracts of M. oleifera leaves (541 ± 1 mg GAE/g dw), but higher than those reported by other researchers [40][41][42][43][44]. Indeed, our TPC findings were higher than those of M. oleifera trees found in the Menzel Lahbib (Gabes-Tunisia) region, whose values ranged from 80.9 ± 1.2 to 136 ± 8 mg GAE/g dw.…”
Section: Total Phenolic and Flavonoid Contentsupporting
confidence: 88%
“…Ethyl acetate and chloroform fractions were the most active ones, containing the highest TPC but not the highest TFC. An 80% methanolic extract prepared with the leaves was also reported by Ayoola et al [40]. However, the extract did not scavenge the radical in a dose-response manner, displaying % inhibition in the range of 59.5% (at 6.25 µg/mL) and 50.4% (at 100 µg/mL).…”
Section: Ros and Rns Scavenging Activitysupporting
confidence: 54%
See 1 more Smart Citation
“…The potential of M. oleifera leaf extract has shown substantial morphological variations and decreased cell viability, with increased ROS generation and inter-nucleosomal DNA fragmentation in the KB cells. [48,49] The Moringa held control for the ROS production and seems to be mark oriented for continuously dividing cells. This could be further verified by the up ruling of caspase 9 and caspase 3 which are part of the apoptotic pathway.…”
Section: Anticancer Propertymentioning
confidence: 99%
“…Moringa oleifera (MO) has been a perfect source of protein and antioxidants, unsaturated fatty acids furthermore vitamins. The nutritional, besides the medicinal characteristic of MO products, have recently appeal attention from various industries world (Ayoola et al, 2019).…”
Section: Introductionmentioning
confidence: 99%